Pengaruh Gaya Kepemimpinan dan Komunikasi Organisasi terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Dinas Perhubungan Kota Pariaman - Mutiara Hijriyah; Marta Widian Sari; Ai Elis Karlinda (Jurnal Transformasi Bisnis Digital, 2026)
This study aims to examine the effect of leadership style and organizational communication on employee performance with work motivation as an intervening variable at the Department of Transportation of Pariaman City. The data analysis method uses questionnaires with a sample of 85 respondents. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) program. The results of this study indicate that: (1) There is a positive and significant effect of leadership style on work motivation, (2) There is no positive and significant effect of organizational communication on work motivation, (3) There is no positive and significant effect of leadership style on employee performance, (4) There is no positive and significant effect of organizational communication on employee performance, (5) There is a positive and significant effect of work motivation on employee performance, (6) Work motivation does not mediate the effect of leadership style on employee performance, (7) Work motivation does not mediate the effect of organizational communication on employee performance. This study provides insights for human resource management in government agencies.